A review of Penthorum chinense Pursh for hepatoprotection: Traditional use, phytochemistry, pharmacology, toxicology and clinical trials. (6th April 2020) - Wang, Anqi; Li, Mingxing; Huang, Huimin; Xiao, Zhangang; Shen, Jing; Zhao, Yueshui; Yin, Jianhua; Kaboli, Parham Jabbarzadeh; Cao, Jiliang; Cho, Chi Hin; Wang, Yitao; Li, Jing; et al.
Abstract: Ethnopharmacological relevance: In China, Penthorum chinense Pursh ( P. chinense ) has been used for hundreds of years traditionally for alleviating symptoms by excessive intake of alcohol as well as in the treatment of traumatic injury, edema and liver diseases. Recently, P. chinense and its extract have been developed into tea, drinks or medicines for treatment of liver diseases, including hepatic virus infections, alcoholic liver disease (ALD), non-alcoholic fatty liver disease (NAFLD) and liver fibrosis. Aim of the study: The main purpose of this review is to provide a critical appraisal of the existing knowledge on the phytochemical data, quality control aspect, pharmacological, as well as toxicological and clinical studies performed on P. chinense, including the identification of scientific gaps. Materials and methods: A detailed literature search was conducted using various online search engines, such as Pubmed, Scopus, Google Scholar, Mendeley, Web of Science as well as China National Knowledge Infrastructure (CNKI) database. Results: In the pharmacological studies, there clearly are links between local/traditional uses and the biomedical investigations. Most pharmacological studies indicated potential liver protective effects in experimental models of chemicals-induced liver injury, acute and chronic alcoholic liver injury, NAFLD, liver fibrosis and viral infection, potentially through antioxidant effects, balancing key liver enzyme levels, inhibition of hepatic virus DNA replication, inhibition of hepatic stellate cells activation and inflammation either in vitro or in vivo . In some models, the effects of P. chinense is comparable with the one of silymarin. Clinical studies have suggested that P. chinense is safe and effective in treating several liver diseases, although most of them are not double-blinded and placebo-controlled studies. Toxicology studies show that P. chinense has no obvious toxicity or side effects in animals or human. Flavonoids, lignans, coumarins, polyphenols and organic acids have been identified. However, only a few studies have investigated the active compounds (mainly flavonoids and lignans) and molecular mechanisms of P. chinense . Conclusion: P. chinense seems to be safe and shows relevant liver protecting effects. Therefore, it might be a promising candidate for developing as new hepatoprotective agents. However, a lack of understanding of the active compounds and mechanisms of action needs further attention. Graphical abstract: Image 1